“Multilingualism“ and identity of Croatian adolescents. - Skelin Horvat, Anita (2010)
The poster discusses a special type of multilingualism among the young where standard language features are used interchangeably with the non-standard ones - both slang and dialcteal forms.
Projekt MZOS
ENG